A multimode and multithreshold approach for energy efficiency in Internet of things systems - Hayfa Ayadi; Ahmed Zouinkhi; Thierry Val; Boumedyen Boussaid; M Naceur Abdelkrim (International Journal of Distributed Sensor Networks)
The IEEE 802.15.4 is designed for wireless personal area networks. Indeed, wireless personal area network turns out to help greatly in maintaining a flexible mode of communication within limited area networks. It is in this context that our present study can be set, in which the beacon-enabled mode is enabled with cluster tree topology to reach the scope of a rather extended network, whereby the network turns out to be clustered into several subgroups. Every single subgroup is characterized by its specific duty cycle which is configured by its correspondent personal area network coordinator. Therefore, many modes are enabled in the same network. Based on a very special mathematical model developed by us for energy consumption, the personal area network coordinator detects the actual level of energy in the battery of node. Then, an interesting comparison is made with the multiple thresholds which are already set. After that, both beacon order and superframe order (the standard IEEE 802.15.4 parameters) are recomputed with reference to the remaining energy.